Editorial: vedolizumab in pregnancy – is gut selectivity as good for baby as it is for mum? Authors' reply. Issue 9 (3rd April 2017) - Mahadevan, U.; Vermeire, S.; Lasch, K.; Abhyankar, B.; Bhayat, F.; Blake, A.; Dubinsky, M.
Abstract : Linked Content This article is linked to Shim and Seow, and Mahadevan et al papers. To view these articles visithttps://doi.org/10.1111/apt.14027 andhttps://doi.org/10.1111/apt.13960 .